Moving bodies, moving images - Yee, Lydia ca. 20./21.Jh; Storey, Grace (Whitechapel Gallery, 2022)
In recent years, music videos, celebrity dance contests and TikTok challenges have shaped the way we experience choreography and dance culture. During the Covid-19 pandemic when live performance events were cancelled, people confined to their homes turned to making and viewing short dance videos: created on mobile phones and designed to be easily replicable and shared on social media platforms. Dance has long had a relationship to film and the screen, from early films of Loie Fuller’s Serpentine Dance (c. 1890s) which highlighted the mediums ability to capture movement and light, to the multi-screen presentations of the choreography of Merce Cunningham transposed into video by Charles Atlas. Visual artists today are inventively reformatting dance and choreographed movement for not only film and the screen but also specifically for the gallery setting, with its repeatable presentation and spatialised viewing conditions. Moving Bodies, Moving Images will feature 10-12 short films by contemporary artists and choreographers that explore the intersection of dance, movement and moving image. These moving image works focus on performing bodies, and unfold as both as individual works but also as collective storytelling, exploring timely topics, ranging from gender politics and desire to bodily memory, resistance and personal healing, to indigeneity and collective identities. The works will be contextualised by three new essays
Impressum: Published on the occasion of 'Moving Bodies, Moving Images', Whitechapel Gallery, London, UK, 12 October 2022 - 8 January 2023
Keywords: Geschichte 2020-2022; Performance -- Künste; Tanz; Dance; Dance in motion pictures, television, etc; Ausstellungskatalog -- Whitechapel Gallery -- 12.10.2022-08.01.2023 -- London